Bringing the single versus multi-patient room debate to vulnerable patient populations: a systematic review of the impact of room types on hospitalized older people and people with neurological disorders. (2nd July 2020) - Shannon, M. M.; Lipson-Smith, R.; Elf, M.; Olver, J.; Kramer, S.; Bernhardt, J.
ABSTRACT: Single-patient rooms are commonly recommended in acute hospital environments. People with neurological disorders, and those who are older, have complex clinical presentations requiring support and recovery for physical, cognitive, and social consequences of their brain injury, and/or chronic health problems. It is currently unknown what type of patient room, or what physical characteristics in such rooms, might be most desirable for the recovery of such people. We explored how hospital single-patient rooms are similar to or different from multi-bed rooms, and how the impact of room type has been measured in this group of people. A systematic mixed studies review was conducted to interrogate these questions. We identified 182 studies (mostly quantitative in design), 19 of which proceeded to formal data extraction. The findings show lack of clarity of salient physical characteristics in either room type for our review population. Importantly, apart from some signal of infection control benefits, our findings do not show evidence to support the use of single-patient rooms with older people and people with neurological disorders for other important outcomes. More investigation of the under-recognized potential of the patient room environment for shaping patient physical, cognitive, and social well-being in specific hospitalized populations is required.